2011
DOI: 10.1016/j.neulet.2011.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Optineurin with amyotrophic lateral sclerosis-related mutations abrogates inhibition of interferon regulatory factor-3 activation

Abstract: Optineurin has been shown to be involved in primary open-angle glaucoma. We recently found that optineurin is involved in familial amyotrophic lateral sclerosis (ALS). On the other hand, optineurin has been shown to inhibit transcription factors related to innate immunity such as NF-κB and interferon regulatory factor-3 (IRF3). In the present study, the effect of ALS-associated optineurin mutations on IRF3 activation was investigated. Optineurin inhibited IRF3 activation induced by melanoma differentiation-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 22 publications
3
29
1
Order By: Relevance
“…More recently, it has been shown that the Q398X and E478G mutations of Optn that have been associated with amyotrophic lateral sclerosis (ALS), a progressive neurodegenerative disorder (see below), have lost their capacity to inhibit IRF3 activation in response to MDA5 or TRIF overexpression. 44 This observation further supports a negative regulatory role of Optn in innate immune defense. Interestingly, the ABIN1 protein has been recently shown to cooperate with TAX1BP1 and A20 to inhibit TBK1-mediated phosphorylation of IRF3 and IFN-B gene expression upon poly(I:C) transfection or virus infection.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…More recently, it has been shown that the Q398X and E478G mutations of Optn that have been associated with amyotrophic lateral sclerosis (ALS), a progressive neurodegenerative disorder (see below), have lost their capacity to inhibit IRF3 activation in response to MDA5 or TRIF overexpression. 44 This observation further supports a negative regulatory role of Optn in innate immune defense. Interestingly, the ABIN1 protein has been recently shown to cooperate with TAX1BP1 and A20 to inhibit TBK1-mediated phosphorylation of IRF3 and IFN-B gene expression upon poly(I:C) transfection or virus infection.…”
supporting
confidence: 54%
“…40 Similarly, the Q398X and E478G ALS-associated mutations reverse the inhibitory effect of Optn on antiviral immunity, but their consequences in other Optn functions have not been yet determined. 44 It has also been proposed that deregulation of secretory cargo release that may occur when Optn or Myosin VI are mutated could be involved in malignant progression of diseases. 34 Thus, defects in secretion of myocilin and angiopoietin-like 7 proteins have been linked to the progression of POAG, and patients with ALS exhibit abnormal secretion of growth hormone and insulin-like growth factor.…”
Section: Subcellular Localization Of Optnmentioning
confidence: 99%
“…4D). Mutations in Optn are a cause of familial ALS (Maruyama et al, 2010), and expression of mutant optineurin leads to deregulation of interferon signaling, suggesting a deleterious role in disease progression (Sakaguchi et al, 2011). We also analyzed changes in cytokine related gene expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the neurotoxic factors, metalloproteinase 12 and optineurin are upregulated in SOD1 G93A microglia [112]. Mutations in optineurin cause fALS [152,153] and deregulate interferon signaling [154], while metalloproteinase inhibition increases survival in ALS mice [155]. More interestingly, in the same study SOD1 G93A microglia also increased the expression of genes related with Alzheimer's, Huntington and Parkinson's diseases but not of genes related with lipopolysaccharide-induced microglial activation [112].…”
Section: Sod1mentioning
confidence: 92%